Interview with Julián Ríos (2005) - Thwaite, Mark (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
Julián Ríos is author of Monstruary, Loves That Bind, Poundemonium and the excellent Larva: A Midsummer Night’s Babel. Here he kindly answers my questions.